Alcohol and energy drinks: individual contribution of common ingredients on ethanol-induced behaviour - Tarragon, Ernesto (Frontiers in Behavioral Neuroscience, 2023)
Since energy drinks (EDs) were sold to the general public as soft drinks and recreational beverages, mixing EDs with ethanol has grown in popularity, particularly among younger people. Given the research that links these drinks with higher risk behaviours and increased ethanol intake, ethanol combined with EDs (AmEDs) is a particularly worrying combination. EDs generally commonly include a variety of ingredients. Sugar, caffeine, taurine and B-group vitamins are almost always present. Studies on the combined effect of ethanol and sugar and caffeine on ethanol-induced behaviours are extensive. Not so much in regards to taurine and vitamins. This review briefly summarises available information from research on the isolated compounds on EtOH-induced behaviours first, and secondly, the combination of AmEDs on EtOH effects. The conclusion is that additional research is needed to fully comprehend the characteristics and consequences of AmEDs on EtOH-induced behaviours.